Technical efficiency analysis of major agriculture production provinces in China: A stochastic frontier model with entropy - Xi Ai (2018)
© Published under licence by IOP Publishing Ltd. Agriculture plays an important role in Chinese economy. This study aims to analyze the agricultural technical efficiency of top 10 agricultural provinces in China. Also, a classical Stochastic Frontier Model (SFM) and a Stochastic Frontier Model (SFM) with entropy are applied in to this study. In our empirical results, we find that the Stochastic Frontier Model (SFM) with entropy is much better than the classical SFM in terms of economic interpretation. From the perspective of technical efficiency, Guangdong Province has been approaching the frontier of agricultural technology efficiency in the past six years. From a national perspective, this means that there is still much room for improvement in technical efficiency and productivity in other provinces. Therefore, we suggest that provinces with technical inefficiency should learn from sample provinces to increase agricultural productivity.